Nutritional composition and antioxidant potential of Chaya leaves (Cnidoscolus aconitifolius) in different cooking methods (Research, Society and Development, 2022)
Unconventional Food Plants (UFP), still little explored due to the lack of knowledge of their properties and forms of use, began to be inserted in the menu of the Brazilian population to obtain nutrients and bioactive compounds that promote good health effects. Among the range of specimens, we have Chaya (Cnidoscolous aconitifolius) a leafy vegetable little studied, which has a high content of minerals and vitamins, besides containing significant protein values. Therefore, the aim of this article is to evaluate the nutritional composition, presence of bioactive compounds and antioxidant capacity of this fresh PANC and submitted to different cooking methods. The most significant protein result was found in the dehydrated leaf (25.70 ± 2.10 mg/100g), on the other hand, the bleached leaf showed a higher amount of phenolics (11.47 ± 1.08 mg/g), and also presented 130.44 ± 41.77mg/g flavonoids, although there is 188.22 ± 25.71mg/g of this nutrient in the fresh leaf, there is no great loss when submitted to the heat source. In relation to antioxidant capacity, there was a reduction of 150.45 ± 0.36µM Trolox/g in ABTS in bleached leaf, and 21.42 ± 0.43µM Trolox/g in FRAP in fresh leaf, but when compared to bleached leaf there were minimal losses, resulting in 20.57 ± 0.49µM Trolox/g. It was possible to conclude that the cooking methods, in order to decrease cyanogenic glycoside levels, they were satisfactory, besides being similar and even exclusive results when compared to the literature, are expressive values, especially when we intend to use them in the form of additional ingredients, in order to promote nutritional fortification and reduce food oxidation.